2017
DOI: 10.1002/phar.1922
|View full text |Cite
|
Sign up to set email alerts
|

Role of Combination Antimicrobial Therapy for Vancomycin‐Resistant Enterococcus faecium Infections: Review of the Current Evidence

Abstract: Enterococcus species are the second most common cause of nosocomial infections in the United States and are particularly concerning in critically ill patients with preexisting comorbid conditions. Rising resistance to antimicrobials that were historically used as front-line agents for treatment of enterococcal infections, such as ampicillin, vancomycin, and aminoglycosides, further complicates the treatment of these infections. Of particular concern are Enterococcus faecium strains that are associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 67 publications
(156 reference statements)
0
58
0
1
Order By: Relevance
“…In vitro studies showed lower MICs for Gramnegative bacteria on exposure to combination drugs than to monotherapies and delay in resistance emergence [30]. Combination therapies possess potential additional benefits of a wider activity spectrum and a synergistic effect and so may be effective in combating infections and improving clinical outcomes [31,32]. Real-life data in patients with multidrug-resistant Gram-negative infections seems to suggest that medical doctors use combination therapies to increase effectiveness and reduce resistance risk [33].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed lower MICs for Gramnegative bacteria on exposure to combination drugs than to monotherapies and delay in resistance emergence [30]. Combination therapies possess potential additional benefits of a wider activity spectrum and a synergistic effect and so may be effective in combating infections and improving clinical outcomes [31,32]. Real-life data in patients with multidrug-resistant Gram-negative infections seems to suggest that medical doctors use combination therapies to increase effectiveness and reduce resistance risk [33].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing use of linezolid, one of the last-resort antibiotics, enhances the selective pressure for developing resistance to it in VRE strains (22). Currently, the speed of research and development of novel antimicrobial agents cannot keep pace with the increasing antibiotic resistance rates, so more and more unconventional combinations for the infection of VRE seem to be attractive options (23). The study conducted by Luther et al showed that the combination of linezolid and gentamicin combination enhanced antimicrobial activity against VRE (20).…”
Section: Discussionmentioning
confidence: 99%
“…This approach fits with the call to action to assess whether single-target antibacterials can be used in combination to overcome resistance (34). Combination antimicrobial therapy, a mainstay for tuberculosis, is becoming increasingly common for other difficult-to-treat infections (35).…”
Section: Discussionmentioning
confidence: 99%